The Phoenix Encounter Method - Woodward, Ian; Padmanabhan, V.; Hasija, Sameer; Charan, Ram (McGraw Hill-Ascent Audio, 2021)
The business landscape is littered with the wreckage of companies that crashed and burned when an apocalypse came-in the shape of new competitive technologies, upstart entrants, demographic shifts, and new world orders. Who can feel safe in firestorm change? The authors of The Phoenix Encounter Method don't advise safety. In fact, their method of leadership thinking requires you to imagine burning your business to the ground-throwing yourself into a firestorm change-and turning the upheaval to your organization's advantage. It can then rise, phoenix-like, from the ashes, stronger and more powerful than ever. Written with a sense of urgency and purposefully radical provocation, The Phoenix Encounter Method represents the forward thinking of legendary business guru Ram Charan and professors from the senior global leadership program of INSEAD, one of the world's top graduate business schools. The resulting methodology, based on analysis of thousands of articles, studies, reports, and academic and business practice, was field tested in real-life Phoenix Encounters conducted with more than fifteen hundred senior executives-from startups and family businesses to legacy companies-representing a broad range of industry and sectors in both developed and developing economies.